Accurate understanding of infertility risk among families of adolescent males newly diagnosed with cancer. Issue 4 (20th February 2018) - Lehmann, Vicky; Flynn, Jessica S.; Foster, Rebecca H.; Russell, Kathryn M.; Klosky, James L.
Abstract: Objective: To examine patient and parent understanding of infertility risk (relative to oncologists' risk ratings) among adolescents newly diagnosed with cancer, and to identify background factors related to inaccurate reporting/estimating. Methods: Male patients (N = 137; aged 13‐21) and their parents completed self‐report questionnaires. Those who reported a fertility‐related conversation with their provider (N = 102 adolescents, N = 74 parents) reported their infertility risk (ie, what oncologist had communicated) and all participants' estimated risk (ie, personal belief). Reports/estimates were compared with oncologists' ratings to assess relative accuracy, and regression analyses assessed potentially related background factors. Results: Participants' agreement of their risk reports with the oncologist was poor (κ = .079/.122 for adolescents/parents), resulting in most adolescents (59.8%) and parents (58.7%) inaccurately reporting risk. Older adolescents were less likely to overreport risk (OR = 0.69; 95% CI, 0.49‐0.97) and parents of sons with the highest Tanner stage were less likely to underreport (OR = 0.28; 95% CI, 0.08‐0.92). Risk estimates were also in poor agreement with oncologists' ratings among adolescents (κ = .040) and parents (κ = .088). Accordingly, incongruent estimates occurred in most adolescents (63.7%) and parents (62.2%), although all reported fertility‐related conversations with their providers. Conclusions: Most adolescents and parents inaccurately reported infertility risk, and more poorly estimated risk. Research is needed to identify additional factors associated with accurate understanding of cancer‐related infertility risk. Providers should be supported with user‐friendly educational tools to promote awareness of infertility risk.